Uncovering the life of your dreams an enlightening story - Schneider, Bruce D. (Wiley, 2018)
Based on the true story of the authors transformational journey, this entertaining tale takes you on a journey of your own toward a more enlightened life filled with abundance, joy, and absolute freedom. --
Print version record and CIP data provided by publisher
Keywords: Spiritual life; Self-acceptance -- Religious aspects; Self-realization -- Religious aspects; Vie spirituelle; Réalisation de soi; Aspect religieux; BODY, MIND & SPIRIT; Inspiration & Personal Growth; BODY, MIND & SPIRIT; Spirituality; General; RELIGION; Christianity; General; RELIGION; Devotional; RELIGION; Spirituality; Self-acceptance; Religious aspects; Self-realization; Religious aspects